2010
DOI: 10.1007/s00015-010-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional stegosaur integument impressions from the Upper Jurassic Morrison Formation of Wyoming

Abstract: Dinosaur skin impressions are rare in the Upper Jurassic Morrison Formation, but different sites on the Howe Ranch in Wyoming (USA), comprising specimens from diplodocid, camarasaurid, allosaurid and stegosaurian dinosaurs, have proven to be a treasure-trove for these softtissue remains. Here we describe stegosaurian skin impressions from North America for the first time, as well as the first case of preservation of an impression of the integument that covered the dorsal plates of stegosaurian dinosaurs in lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
(52 reference statements)
2
30
0
Order By: Relevance
“…(2005) and Christansen and Tschopp (2010) have also suggested that plates were covered in keratin. Particularly, Christansen and Tschopp (2010) noted that they found what was possibly keratin on a plate. The external and internal vascular canals in plates and spikes probably contribute to the production of the keratin sheath.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2005) and Christansen and Tschopp (2010) have also suggested that plates were covered in keratin. Particularly, Christansen and Tschopp (2010) noted that they found what was possibly keratin on a plate. The external and internal vascular canals in plates and spikes probably contribute to the production of the keratin sheath.…”
Section: Discussionmentioning
confidence: 97%
“…Main et al. (2005) and Christansen and Tschopp (2010) have also suggested that plates were covered in keratin. Particularly, Christansen and Tschopp (2010) noted that they found what was possibly keratin on a plate.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible, therefore, that the section exposed at the Red Canyon Ranch may correlate with the middle part of the Morrison Formation at Red Gulch ( Fig 4 ). The Howe and Howe-Stephens quarries, which are close by and have both produced a diverse range of dinosaur taxa, also appear to be from the middle part of the Morrison Formation in this area [ 5 , 6 ]. A radiometric date of 151.5±3 million years was obtained from a bentonite near the base of the Morrison Formation at the nearby Red Gulch dinosaur tracksite [ 7 ], indicating that the entirety of the Morrison Formation in this area could have been deposited during the Tithonian.…”
Section: Geological Settingmentioning
confidence: 99%
“…2). Kvale et al (2001) interpreted a second site approximately 10 m higher in stratigraphy (Howe-Stephens Quarry, see Schwarz et al 2007b;Christiansen & Tschopp 2010) as being of 147 Ma in age. This implies a latest Kimmeridgian to earliest Tithonian age for the Howe Quarry.…”
Section: Geological Settingmentioning
confidence: 99%